Mechanics. - Datta, Somnath (2012)
Mechanics meets the requirement for an ideal text on Mechanics for undergraduate students. The book gives the readers a better understanding of topics like Rectiline Motion, Conservation of Energy and Equation of Motion. Provides a good number of examples with good use real time illustration and exercises for practice and challenge. The book comprehensively covers of Newton's Law of Motion, Conservation Laws of momentum, energy and Law of gravitation and includes 180 worked out examples and 185 end of chapter exercises.
9.8 A Closer Look at Planetary (Satellite) Orbits.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books